Extracorporeal Immunomodulation Treatment and Clinical Outcomes in ICU COVID-19 Patients - Lenar T. Yessayan, MD, MS; Javier A. Neyra, MD, MS; Angela J. Westover, BS; Balazs Szamosfalvi, MD; H. David Humes, MD (Critical Care Explorations, 2022)
OBJECTIVES:. To evaluate safety and clinical outcomes of extracorporeal immunomodulation treatment with a selective cytopheretic device (SCD) in COVID-19 ICU patients with multiple organ failure. DESIGN:. Two-center, prospective, single-arm treatment clinical trial. SETTING:. ICUs at two academic medical centers between September 2020 and July 2021. PATIENTS:. Twenty-two COVID-10 patients in the ICU with acute respiratory distress syndrome who required mechanical ventilation. Nearly all included patients in the intervention group except one had acute kidney injury requiring continuous renal replacement therapy (CRRT). Sixteen subjects meeting enrollment criteria were selected as contemporaneous controls from a concurrent prospective registry CRRT trial. INTERVENTION:. Treatment with an SCD integrated into a continuous renal replacement extracorporeal blood circuit for up to 10 days to provide autologous leukocyte cell processing to immunomodulate the hyperinflammatory disease state of COVID-19. MEASUREMENTS AND MAIN RESULTS:. SCD treatment in COVID-19 ICU patients with multiple organ failure demonstrated an acceptable safety profile with no device-related serious adverse events. Treatment of these patients resulted in the selective removal of highly activated circulating leukocytes as determined by flow cytometry. Significant reductions were observed in the elevated plasma levels of eight cytokines and biomarkers, including interleukin (IL)6, IL15, IL10, and soluble ST2, which are predictive of mortality in COVID-19 patients. Significant improvements of leukocytosis and Po2/Fio2 ratios occurred during treatment not observed in the control group. SCD-treated subjects had a reduction in 60-day mortality of 50% compared with 81% in the control cohort. The subjects who received greater than 96 hours of SCD treatment, per protocol, had a further reduction in mortality to 31% (p < 0.012). CONCLUSIONS:. Extracorporeal immunomodulation therapy with an SCD demonstrated safety without any device-related serious adverse events. As a rescue therapy in COVID-19 ICU patients progressing to multiple organ failure despite maximal pharmacologic and organ support interventions, SCD treatment resulted in improved clinical outcomes. This autologous leukocyte cell processing technology may provide a new approach in the treatment of unremitting hyperinflammation of COVID-19.